Paghanduraw history of Patnongon, Antique (ca. 1400s - 1945). - Legaspi, Merle M. (2004.)
This is a study of the history of Patnongon (including the town of Belison being part of it) from the pre-Spanish period to Japanese period focusing on the events that transpired during those periods which affected the growth and development of the said locale. This study aims to; 1.) describe the early settlements-its locations, its terrain and river system and the role played in settling the place and early experiences of the people against Moro piratical raids; 2.) present early events that took place upon meeting of the natives with the Spaniards and the eventual formation of the community; 3.) examine the initial reactions of the Patnongon upon the American occupation of the town and the improvements introduce by the colonizer and 4.) find out how the people reacted and lived during the Japanese occupations., sources used were categorized into primary and secondary. Primary sources were based on interviews with the war veterans, ordinary town's folk, and people who experienced living under the said periods. Interviews were conducted in vernacular and in either formal or informal set-up with guide questions. Secondary data were taken from books, materials such as old maps, and manuscripts. The chapters on pre-Spanish and Spanish periods were largely taken from Mr. Andres Elio's Maragtas kang Patnongon (History of Patnongon) since that is the only reliable source. In addition, no one can testify about pre-Spanish and Spanish periods. Mr. Elio is a local historian and based his writings from the manuscripts of his father (Cornelio Elio) born in 1851 and was a church fiscal and bookkeeper for twenty-eight years. Another is from the manuscript of the former municipal president Mr. Felix Mondejar. The validity of the data presented in the said books was crosschecked through interviews with the residents. The rest of the chapters were based largely on interviews. The early inhabitants of Patnongon were the Maghats. They lived near the rivers off Ipayo and Patnongon. But due to the frequent Moro attacks, they settled in the hinterlands as far as in the foot of Magpungay Mountain. They were animistic and believed that "Bulalacao" is the supreme god and "Bangotbanua" is the high priest. They engaged in salt making. The meeting of the Maghats and the Spaniards happened when the latter drop their anchor near the mouth of Catuayan River which, happened to be the location of Maghats salt beds. However, after nearly a week of being friends, the Maghats killed the Spaniards for unknown reasons. Maybe the Spaniards did something that triggered that incident. The incident came to the attention of the priest who went to the Bugasong and proceeded to investigate it. Upon confirmation, the Spanish authorities sent its soldiers to talk with the Maghats regarding their plans to transfer them to the lowlands. This intention was made known to the only Maghats left in the area named Ado (Pedro alagos). Eventually, the comisarios were sent to Patnongon and in due time some of the Maghats settled in the lowlands. On the process, Patnongon was established first as a funds and then as a visita or religious unit before it became a town. Under Spanish rule, the inhabitants were subjected to harsh policies such as conscription for the military unit and forced labor, paying tributes among others. Later, some of the natives were allowed to held office but the inhabitants found out that they became abusive of their power. These grievances found venue when the revolution broke out. The inhabitants joined in the resistance movement against the Spaniards. When the Americans came to Patnongon, they met an initial resistance coming from the revolutionaries, which they labeled as `insurrectos'. The encounter that transpired in macarina ended the resistance movement in Patnongon. The Americans improved the sanitation condition of the town since during the previous years there was epidemic. The natives largely anticipated the entry of the Japanese in Patnongon but when the actual day of encroachment occurred, they were caught off handed. The inhabitants fled and hid in the areas that they considered safe from Japanese encroachment. In Belison, the evacuation sites were in Igcabugao, Bacay, and Huna; on the other hand in Patnongon were located in its hinterlands like Samalague, Macarina, La roioja, and Carit-an. The inhabitants experienced unprecedented fear and hardship during this period. But the situation calmed down when the Japanese stationed themselves in the old stone church and through the efforts of mayor Anselmo Alvaniz. He dually collaborated with the Japanese and guerillas. This was true also in the case of the Japanese spies.
Research Study (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: History -- Antique -- 1400 -1945.